The Optimization of Perovskite Solar Cells from Power Conversion Efficiency and Operational Stability - Liu, Pengyun (Curtin University, 2020)
This thesis aims to improve the power conversion efficiency and operational stability of CH3NH3PbI3-based perovskite solar cells and CsPbIBr2-based perovskite solar cells via the strategies of additive engineering and composition engineering. A variety of characterization techniques have been utilized to investigate the influences of the employed strategies on the properties of perovskite films and the photovoltaic performance of perovskite solar cells to gain a better understanding of the internal mechanism.